Employee onboarding and satisfaction in US manufacturing companies. Issue 2 (30th December 2021) - Kirchner, Michael; Stull, Faith
Abstract : Purpose: The purpose of this study was to identify primary issues related to employee onboarding and satisfaction in US-based manufacturing companies. Design/methodology/approach: In total, 19 focus groups using semi-structured interviews with senior management, middle management, tenured employees and new employees were conducted with personnel from five manufacturing companies located in the Midwest USA. Onboarding procedures, training manuals, employee satisfaction surveys and performance evaluations were subsequently reviewed. Findings: Insufficient onboarding, poor communication and a perceived lack of support were reported as satisfaction concerns by manufacturing employees. In addition, management had vastly differing perspectives regarding the work environment when responses were contrasted with those from new or tenured employees. Originality/value: This paper reveals contributing factors that influence satisfaction early and throughout an employee's tenure with small- to medium-sized US manufacturing companies.